Elemental Signatures of Xianfeng Tongbao: XPS Evidence of Fiscal Crisis and Currency Devaluation in Late Qing China - He, Yangkun (Simen Owen Academic Proceedings Series, 2026)
The Xianfeng reign (1851-1861) was marked by severe fiscal crisis and monetary instability in Qing China, when official and privately minted coins circulated simultaneously. While numismatic and historical studies have described this phenomenon, they often lack systematic material analysis, and scientific investigations of alloy composition rarely extend to socio-economic interpretation. This study bridges the gap by employing X-ray photoelectron spectroscopy (XPS) to compare the elemental composition of an official and a privately minted Xianfeng Tongbao coin. Surface cleaning, rust removal, and high-resolution XPS scans were conducted at three random points for each specimen, followed by CasaXPS peak fitting to quantify Cu, Zn, Pb, and Sn contents. Results show that official coins maintained high Cu content with stable Zn and Sn proportions, ensuring structural stability, whereas private issues exhibited reduced Cu and elevated Zn and Pb, with inconsistent Sn, leading to weaker alloys. These compositional differences directly reflect resource scarcity, fiscal weakness, and declining state control. The findings demonstrate that microstructural chemistry can serve as material evidence of macroeconomic crisis, contributing both to numismatic science and to economic history, while offering methodological value for archaeology and heritage conservation.